A review on the edible bird's nest quality and manufacturing standards of the three largest exporting countries in the world - Zulkefe, Nurin Naziha; Ahmed Ibrahim, Mohamed; Azuan, Nor Fateha; Ee Ch'ng, Soo; Ismail, Norsharina; Abu Bakar, Md Zuki; Chan, Kim Wei (John Wiley and Sons Inc, 2024)
Edible bird’s nest (EBN) is an animal product with the world’s highest market price due to its value. Te nests are made exclusively from the saliva secreted by swiftlet, a species of bird native to Southeast Asia. For over a century, EBN has been consumed in many parts of the world as a nutritious food. Te high economic value of EBN attracts people to invest and engage in the bird nest industry. Currently, China is the largest importer of EBN, while Southeast Asian countries, namely, Indonesia, Malaysia, and Tailand, are the three largest exporters of EBN. An analysis of EBN’s compositions from most previous studies revealed that protein, carbohydrate, moisture, fat, and ash in EBN from the three central producing countries did not have apparent diferences in their origins and were comparable to each other. Before 2011, EBN trade with China was unregulated. Consequently, the industry encountered problems due to the high nitrite content in EBN. Since then, these three countries have taken great measures to deal with this food safety issue and formulated a standard operating procedure (SOP) to meet the specifc criteria listed for exporting EBN to China. Hence, this review discusses the quality and safety standards of EBN from the three countries and China’s standards for EBN importation.